Research on the charging periods of the ultra-shallow play in front of the Hashan area, northwestern margin of the Junggar Basin - WANG Qianjun; ZHOU Jian; ZHANG Faqiang; YU Hongzhou; WU Qianqian; LU Hongli; LIU Qingxin; ZHOU Yu; CHENG Ming; YAN Jianzhao; LYU Yanfang (Dizhi lixue xuebao, 2025)
Objective  The Hala’alat Mountain front-overthrust belt, renowned for its abundant hydrocarbon resources, is characterized by multi-layer oil-bearing systems and intricate source-reservoir relationships. Ultra-shallow strata have emerged as an important domain for resource evaluation and exploration in this region. However, the timing of hydrocarbon charging and adjustment processes and the complex accumulation mechanisms of ultra-shallow reservoirs remain inadequately understood, posing significant challenges for exploration planning and appraisal programs. This study endeavors to unravel the genetic characteristics, accumulation stages, and dynamic mechanisms of ultra-shallow reservoirs in the Hala’alat Mountain front, with the goals of enhancing the theoretical framework for hydrocarbon enrichment patterns in structurally complex zones and providing actionable insights for future exploration endeavors.   Methods  To achieve this objective, an integrated suite of analytical techniques was meticulously employed. Homogenization temperature measurements and salinity analysis of fluid inclusions were conducted to decipher thermal histories and fluid evolution. Quantitative grain fluorescence (QGF) analysis was utilized to track hydrocarbon migration pathways and accumulation dynamics. Calcite U–Pb geochronology provided precise temporal constraints for thermal events and hydrocarbon charging episodes. These methods were systematically applied to reservoir rock samples, enabling a comprehensive investigation of fluid inclusion characteristics, paleo-temperature evolution, and paleo-fluid interfaces. By constraining the thermal event chronology, we aimed to reconstruct the intricate hydrocarbon charging and adjustment processes that have shaped the current reservoir configuration.   Results  (1) The analysis revealed a diverse array of fluid inclusion types, with variations in fluorescence color and intensity indicative of multiple stages of hydrocarbon charging, each with a distinct maturity levels. The homogenization temperatures of aqueous inclusions exhibited two predominant intervals: 70–90°C and 100–130°C. These temperature ranges correspond to distinct thermal episodes, reflecting varying paleo-thermal regimes that influenced hydrocarbon maturation and migration. (2) The QGF profiles provided compelling evidence of dynamic hydrocarbon migration processes, showcasing multiple northward adjustments and accumulations over geological time scales. Notably, Jurassic strata displayed continuous charging characteristics, suggesting prolonged hydrocarbon influx, while Cretaceous reservoirs exhibited late-stage charging patterns, reflecting differential hydrocarbon charging histories across stratigraphic units. This stratigraphic variation in charging behavior offers crucial insights into the temporal and spatial distribution of hydrocarbons within the study area. (3) Calcite U–Pb dating identified two major thermal events at approximately 133 Ma (Early Cretaceous) and 73 Ma (Late Cretaceous). These events are temporally correlated with significant tectonic activities in the study area, including regional compression and fault reactivation. (4) The integration of homogenization temperatures, QGF data, and U–Pb ages revealed a two-phase hydrocarbon charging history. The first phase occurred during the Early Cretaceous (133 Ma), characterized by initial hydrocarbon accumulation driven by regional tectonic compression. The second phase took place during the Late Cretaceous (73 Ma), marked by structural adjustment and hydrocarbon redistribution. These phases were primarily driven by tectonic forces that facilitated vertical migration and redistribution of hydrocarbons into ultra-shallow traps, highlighting the interplay between tectonic events and hydrocarbon accumulation.   Conclusions  The ultra-shallow reservoirs in the Hala’alat front have undergone two critical accumulation phases: the Early Cretaceous initial charging phase and the Late Cretaceous structural adjustment phase. Hydrocarbon migration pathways were predominantly controlled by fault systems, which acted as migration carriers. The northward adjustments were facilitated by differential uplift and the caprock integrity, ensuring the preservation of hydrocarbons within the reservoirs. The coupling of fluid inclusion thermometry, QGF, and U–Pb dating has proven to be a robust and innovative toolkit for resolving multi-stage accumulation processes in complex thrust belts. This methodological integration not only enhances our understanding of hydrocarbon accumulation mechanisms but also provides a precise framework for identifying and dating these events. This study establishes a novel and comprehensive methodology for deciphering multi-phase hydrocarbon accumulation in tectonically active regions. [ Significance ] By offering critical insights into the timing, pathways, and driving mechanisms of hydrocarbon charging, this study provides a solid foundation for predicting ultra-shallow reservoir distributions in similar geological settings. The integration of chronostratigraphic and fluid dynamic analyses advances the theoretical understanding of hydrocarbon enrichment mechanisms in foreland thrust belts, with direct implications for exploration strategies and resource evaluation in analogous basins. Furthermore, the methodological framework developed in this study can be adapted and applied to other complex structural zones, potentially revolutionizing our approach of hydrocarbon exploration in challenging geological environments.